Aging, senescence, and cutaneous wound healing—a complex relationship - O’Reilly, Steven; Markiewicz, Ewa; Idowu, Olusola C. (Frontiers in Immunology, 2024)
Cutaneous wound healing is a complex multi-step process that is highly controlled ensuring efficient repair to the damaged tissue and restore tissue architecture. Multiple cell types play a critical role in wound healing and perturbations in this can lead to non-healing wounds or scarring and fibrosis. Thus, the process is tightly regulated and controlled. Cellular senescence is defined as a irreversible cell cycle arrest and associated with various phenotypic changes, metabolic alterations and coupled to a secretory program. Its role in wound healing, at least in the acute setting, appears to help promote appropriate mechanisms leading to complete restoration of tissue architecture. Opposing this is the role of senescence in chronic wounds where this can lead to either chronic non-healing wounds or fibrosis. Given the two opposing outcomes of wound healing in either acute or chronic settings this has led to disparate views on the role of senescence in wound healing. This review aims to consolidate knowledge on the role of senescence and ageing in wound healing examining the nuances of the roles in the acute or chronic settings and attempts to evaluate the modulation of this to promote efficient wound healing.